GHG Inventory Data for Kenya’s Crop Subsector for Transitioning to Tier Two Reporting. - Maina, Obadiah Mwangi; Kioko, Angela Wayua; Jalango, Dorcas Anyango; Kinyua, Ivy Wambui; Nyawira, Sylvia Sarah (2025)
GHG Inventory Data for Kenya’s Crop Subsector Transitioning to Tier Two Reporting. Methodology: Data collection by the use of surveyCTO tool in five counties. Taita Taveta, Makueni, Murang'a, Baringo, and Nyamira between August and September. (2024-11)